Drug Information Resources in Iraqi Community Pharmacies (Conference Paper) # - Mohanad Yasir Radeef; Khalid Saud Saleh (College of Pharmacy University of Baghdad, 2023)
Abstract      Drug information resources are the information that is used in medications discovery, utilization, and management. Little information about different types of resources used by Iraqi community pharmacists is known. Therefore, the objectives were to determine drug information resources' type do the pharmacists used and the common drug information questions they faced during their work in community pharmacy. A cross-sectional descriptive study was conducted in different Iraqi provinces and online self-reported survey was introduced through Google Form Software to an appropriate sample of graduated pharmacists who were working in a private community pharmacy and having at least one year of experience between February 27 and May 15, 2021. The researchers received 201 usable surveys. British National Formulary was used by 47% of the surveyed pharmacists to find specific information, followed by "Pharmacotherapy(s) and Applied Therapeutics" (16.9% for both). On the other hand, internet was used by 93% of the surveyed pharmacists and Google search engine (65%) and Medscape application (62%) were frequently surfed to find specific drug information and 81% of pharmacists trusted in this information and passed them to consumers. Safety of drugs during pregnancy and lactation periods was the most frequently question received from the patients (60.7%). In conclusion pharmacists prefer to surf specific internet websites to collect specific information about medicines and they referred to pharmaceutical textbooks if available at their pharmacies to get such information. The pharmacist is the person who is more often accessed by patients and the patients follow pharmacist's instruction for specific drug related questions.